Ptilodactyla crenatostriata Redtenbacher, 1868 (Coleoptera: Ptilodactylidae) transferred to Phytocerum Costa, Vanin, Lawrence & Ide, 2003 (Coleoptera: Cerophytidae) - Kundrata, Robin; Jäch, Manfred (Zootaxa, 2017)
Ptilodactyla crenatostriata Redtenbacher, 1868 (Coleoptera: Byrrhoidea: Ptilodactylidae) described from Rio de Janeiro, Brazil, is transferred to the genus Phytocerum Costa, Vanin, Lawrence & Ide, 2003 (Coleoptera: Elateroidea: Cerophytidae). Based on the examination of the holotype, deposited in the Naturhistorisches Museum Wien, Austria, Phytocerum crenatostriatum comb. nov. is redescribed and its main diagnostic characters are figured. It is similar to P. birai Costa, Vanin, Lawrence & Ide, 2003 and P. cayennense (Bonvouloir, 1870). An updated checklist of the extant and fossil Cerophytidae of the World is provided.